Metformin, Chlorpropamide, and Glibenclamide: Interactions with Metal Ions and Cyclodextrins - González-Barbosa, Jeovani; Hipólito-Nájera, Adrián R.; Gómez-Balderas, Rodolfo; Rodríguez-Laguna, Norma; Moya-Hernández, Rosario (Mini-Reviews in Organic Chemistry, 2024)
In the field of Chemistry, it is essential to study molecules with biological activity on chronic degenerative diseases to design drugs that help to improve the health of people with diseases such as diabetes, arterial hypertension, rheumatoid arthritis, cancer, among others; and that in turn may have fewer side effects. Diabetes mellitus is a serious metabolic disorder that affects millions of people worldwide; due to the illness severe affectations, there is a great interest in improving pharmacological treatments (hypoglycemic drugs) used in this disease. Nowadays, it has been reported that metallodrugs and drug-cyclodextrin inclusion compounds have higher therapeutic activity than free drugs, with fewer side effects. In the present work, we compile, analyze, synthesize and discuss published information on the hypoglycemic drugs Metformin (C4H11N5), Chlorpropamide (C10H13ClN2O3S) and Glibenclamide (C23H28ClN3O5S) complexed with metal ions or included in cyclodextrins in aqueous solution. Nowadays, this type of complex should be widely studied for the treatment of type 2 diabetes mellitus. Physicochemical and thermodynamic properties, synthesis, mechanism of action, as well as analytical studies on the interaction of hypoglycemic agents with different complexing agents, are discussed.
Keywords: diabetes mellitus